Utilisation of salty whey ultrafiltration permeate with electrodialysis. (December 2019) - Talebi, Sahar; Kee, Esther; Chen, George Q.; Bathurst, Karren; Kentish, Sandra E.
Abstract: Salty whey is a waste by-product that incurs increasingly high disposal costs for the dairy industry. This study investigated electrodialysis of the ultrafiltration permeate of salty whey as either a concentrate for the treatment of sweet whey or as a source of lactose and salt. The type of concentrate (0.1 m NaCl or salty whey permeate) did not affect the rate of sweet whey demineralisation or the energy consumed per tonne of whey, but less sodium and more divalent cations were removed when salty whey permeate was used as the concentrate. Salty whey permeate could be effectively demineralised using either 0.1 m NaCl or a second stream of salty whey permeate as the concentrate. The concentrate purity could be enhanced using monovalent selective membranes without increasing the energy consumption of the process (3.2 ± 0.3 kWh per kg of NaCl removed from the diluate at 15 V).